2020
DOI: 10.1016/j.ijheatfluidflow.2020.108658
|View full text |Cite
|
Sign up to set email alerts
|

Hairpin vortices in the largest scale of turbulent boundary layers

Abstract: We have conducted direct numerical simulations of a turbulent boundary layer for the momentum-thickness-based Reynolds number Re θ = 1804600. To extract the largestscale vortices, we coarse-grain the uctuating velocity elds by using a Gaussian lter with the lter width comparable to the boundary layer thickness. Most of the largestscale vortices identied by isosurfaces of the second invariant of the coarse-grained velocity gradient tensor are similar to coherent vortices observed in low-Reynolds-number regions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…These observations are similar to turbulence in a periodic cube (Goto 2008; Goto et al. 2017), turbulent boundary layers (Motoori & Goto 2019, 2020) and turbulent channel flow (Motoori & Goto 2021). However, the turbulent wake is more complex than these flows because the largest-scale vortices are different depending on regions.…”
Section: Hierarchy Of Coherent Vorticessupporting
confidence: 60%
“…These observations are similar to turbulence in a periodic cube (Goto 2008; Goto et al. 2017), turbulent boundary layers (Motoori & Goto 2019, 2020) and turbulent channel flow (Motoori & Goto 2021). However, the turbulent wake is more complex than these flows because the largest-scale vortices are different depending on regions.…”
Section: Hierarchy Of Coherent Vorticessupporting
confidence: 60%
“…2014) have revealed three-dimensional flow structures in single-phase wall turbulence. Our previous studies also revealed the generation mechanism of the hierarchy of coherent structures in a turbulent boundary layer at (Motoori & Goto 2019, 2020) and turbulent channel flow at (Motoori & Goto 2021). Wall-attached vortices, i.e.…”
Section: Introductionmentioning
confidence: 63%
“…This technique was used by several authors (e.g. del Álamo et al 2006;Lozano-Durán et al 2012;Osawa & Jiménez 2018;Motoori & Goto 2020). More concretely, we tag the same label to the neighbouring connected grid cells satisfying the condition in order to count the number of the identified vortices and to estimate the volume for different values of Q 10), since each object shrinks, the number again decreases.…”
Section: Appendix a Percolation Analysismentioning
confidence: 99%